Seroepidemiological survey of Mycoplasma pneumoniae in children aged 0–6 years in Huzhou city (October–December 2023): a seasonal cross-sectional study - Liu, Yan; Wang, Yuda; Zhang, Chao; Luo, Xiaofu; Zhang, Zizhe; Hu, Xiaoqiang; Shen, Jianyong (Frontiers in Pediatrics, 2025)
ObjectiveThe study aimed to investigate the seroprevalence and geometric mean concentrations (GMCs) of Anti-Mycoplasma pneumoniae immunoglobulin G (Anti-MP-IgG) among children aged 0–6 years in October-December 2023 in Huzhou City, China, and explore the influence of age and gender on seropositivity.DesignAnti-MP-IgG levels were categorized into negative (<24 AU/mL), borderline (≥24 AU/mL and <36 AU/mL), and positive (≥36 AU/mL) groups. The GMCs and prevalence rates were analyzed according to age and gender. Linear regression and logistic regression analyses were performed to assess trends and associations.ResultsA total of 526 participants were enrolled in the study. The overall GMC of Anti-MP-IgG was 6.21 AU/mL (95% CI: 5.39–7.15). While there was no significant difference in GMCs between genders (P = 0.862), a significant increasing trend in GMCs was observed with age (F = 16.649, P < 0.001). The proportion of positive Anti-MP-IgG levels increased significantly with age, from 10.20% in 0-year group to 32.50% in 6-years group (P < 0.001). Logistic regression revealed that age was significantly associated with Anti-MP-IgG positivity (OR: 1.37, 95% CI: 1.21–1.56, P < 0.001), while gender was not.ConclusionsThe seroprevalence and GMCs of Anti-MP-IgG showed a clear age-related increasing trend, indicating age as a significant factor for seropositivity in children aged 0–6 years. Further studies are needed to explore underlying mechanisms and the implications for public health strategies.